Unraveling the reservoir heterogeneity of the tight gas sandstones using the porosity conditioned facies modeling in the Whicher Range field, Perth Basin, Western Australia - Kadkhodaie-Ilkhchi, R.; Kadkhodaie, A.; Rezaee, M. Reza; Mehdipour, V. (Elsevier, 2019)
Tight sandstones of the late Permian Willespie Formation constitute an important reservoir rock in the Whicher Range gas field of the Perth Basin. The sandstones under the effect of sedimentary conditions and diagenesis show some degree of heterogeneity reflecting in reservoir properties and production history. The Willespie Formation consists of fine to coarse-grained and gravelly feldspathic sandstones intercalated with shale, siltstone and coal, deposited in a meandering river system. Different diagenetic processes including compaction, cementation (authigenic clays, calcite and siliceous) and dissolution have severely affected the pore system properties of the reservoir sandstones, as they are considered as tight sandstones. In this study, three-dimensional modeling of reservoir sandstones has been performed using stochastic modeling algorithms for facies and porosity properties. A preliminary facies analysis of the main reservoir rocks based on core and well logs data provided the basis for reservoir zonation and modeling. Regarding the close relationship between acoustic impedance with depositional/diagenetic characteristics of reservoir facies and their porosity, this seismic attribute was used as a secondary parameter in porosity modeling. The results indicate a close relationship between sedimentary characteristics and reservoir properties. Based on the extracted models, most of the porous zones are related to the clean and coarse sandstones of the fluvial channels accumulating in the upper parts of the reservoir. In fact, initial sedimentary characteristics have the main impact on the distribution of reservoir zones, their thickness and continuity in the field and controlling large-scale reservoir heterogeneity which has been enhanced by the effect of diagenetic processes on the pore system properties and controlling the internal reservoir heterogeneity in next stages. Distinctive variability in reservoir properties towards the upper reservoir units and also among different wells can be considered for optimizing exploration and development targets of the field.